Perceptions of Postpartum Mothers of Their Experiences as a Patient During COVID-19 Crisis: A Phenomenological Study. (December 2022) - Jacob, Ani; Thomas, Tesi; Antretter, Jessica
Coronavirus disease-2019 (COVID-19) pandemic led to drastic changes in in-hospital healthcare delivery causing major policy and protocol changes regarding labor and delivery and postpartum care of maternity patients. We strove to describe and understand the perceptions of laboring and postpartum mothers' care received through interviews in a hospital during the COVID-19 pandemic. Using a phenomenological study design, we interviewed 13 postpartum mothers. Five major themes and 10 subthemes were extracted. Major themes, both positive and negative, included genuine concern of caregivers, adverse breastfeeding experiences, feeling of being left alone, loss of expectations, and uncertainty. Primipara women had a major impact on their psychological well-being and breastfeeding experiences. Isolation and feelings of left alone adversely affect postpartum mothers' coping, newborn care, bonding, meeting basic needs of sleep and hygiene, breastfeeding experiences, and potential postpartum recovery and psychosocial well-being including fear of future pregnancies. Therefore, "partner presence" throughout the labor and delivery and postpartum period should be a "call to action" for the nurses, especially with first-time mothers.